Phenomenological configurations of workplace bullying: A cluster approach. (1st December 2019) - Paciello, Marinella; Fida, Roberta; Tramontano, Carlo; Ghezzi, Valerio; Barbaranelli, Claudio
Abstract: The present study represents an innovative contribution combining an articulated description of phenomenological manifestations of bullying with an in-depth picture of individual processes operating within the regulative system. Phenomenological configurations of bullying were identified considering not only exposure to and types of bullying, but also two of its main correlates: health problems and deviant behaviour. Moreover, the study examined how these configurations differ in terms of discrete negative emotions experienced in relation to work, coping strategies, and moral disengagement. Results from a sample of 1019 employee (53.6% women) support a 5-cluster solution: not bullied with no symptoms and no misbehaviour (39.9%); not bullied but with symptoms and some misbehaviour (23.9%); targets exposed to limited work-related negative acts, with no symptoms and some misbehaviour (22.3%); targets of work-related bullying with symptoms and misbehaviour (9.6%); and victims with high symptoms and high misbehaviour (4.4%). Moreover, the examination of clusters in relation to individual dimensions highlights the pivotal role of negative emotions and emotional regulation, independently from exposure to workplace bullying. Further, in more severe cases, moral disengagement and compensatory behaviour play an equally important role suggesting the weakening of individuals' behavioural regulation.